Psychological Analysis of Finch and Violet in Jennifer Niven’s All The Bright Places - Taufiqul Hakim Al Roziq (Fakultas Ilmu Budaya, 2025)
This study uses a literary psychology approach based on Wilbur S. Scott's theory to analyze Jennifer Niven's novel All The Bright Places. The main focus of this study is to analyze the characters of Theodore Finch and Violet Markey from a psychological perspective, particularly trauma, internal-external conflict, and how each individual responds to their problems. The next focus of this research is to examine how Niven's personal emotional experiences influenced the creation of characters and narratives in the novel, particularly the characters of Finch and Violet. Through a creative psychology approach and a study of the author's life, the author investigates the connection between Niven's traumatic experiences and the development of fictional characters, particularly in depicting trauma, inner conflict, and the psychological healing process of the characters. The analysis is conducted qualitatively by combining primary data from the novel's narrative and secondary data from personal blogs, media interviews, and relevant journals. The research findings reveal that the characters of Finch and Violet reflect deep psychological conflicts, such as the desire to disappear, identity crises, guilt over surviving, and the impact of unsupportive family and social environments. This characterization aligns with Jennifer Niven's personal experience of losing someone she once loved, which she then emotionally channeled into the story. Through a literary psychology approach, this study highlights the importance of the author's psychological background in shaping emotionally charged and meaningful literary works.
REupload File Repositori 5 Februari 2026_yudi/Rega
Keywords: Jennifer Niven's; Niven's personal